Analysis of the Influence of Education Standardization and Age on Regional Head Candidates - Aulia, Nur Fitri; Nurvasya, Fadila (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to analyze the influence of education standardization and age on the quality of leadership of regional head candidates in Indonesia. Democracy gives the people the right to choose their leaders, including regional heads. Therefore, the election of quality regional heads is the main key to realizing good governance and effective regional development. This study uses multiple linear regression methods to analyze the relationship between education standardization (X1) and age (X2) on the leadership performance of regional head candidates (Y). Data was collected through questionnaires distributed to 42 respondents and literature studies from various sources. Validity test results showed that 10 out of 12 questionnaire items were valid, while reliability testing yielded a Cronbach's Alpha value of 0.736, indicating high reliability. The results indicate that there is no significant influence of education (X1) on the leadership performance of regional head candidates with a significance value of 0.993 > 0.05. However, the age variable (X2) has a significant influence on the leadership performance of regional head candidates with a significance value of 0.000 < 0.05. Simultaneously, both variables together have a significant effect on the qualifications of regional head candidates with an F value of 9.644 and significance of 0.000 < 0.05.